Involvement of Exogenous N-Acyl-Homoserine Lactones in Spoilage Potential of Pseudomonas fluorescens Isolated From Refrigerated Turbot - Li, Tingting; Wang, Dangfeng; Ren, Likun; Mei, Yongchao; Ding, Ting; Li, Qiuying; Chen, Haitao; Li, Jianrong (Frontiers in Microbiology, 2019)
Some bacteria can modulate their spoilage potential by responding to environmental signaling molecules via the quorum sensing (QS) system. However, the ability of P. ﬂuorescens, the specific spoilage organism (SSO) of turbot, to response to environmental signaling molecules remains unclear. This study investigated the effects of six synthetic N-acyl homoserine lactones (AHLs) on typical behaviors mediated by QS in P. ﬂuorescens, such as biofilm formation and extracellular protease activity. Total volatile basic nitrogen (TVB-N) was used as a spoilage indicator to evaluate quality changes in AHL-treated turbot fillets during storage. The results confirm the enhancing effect of environmental AHLs on QS-dependent factors of P. ﬂuorescens and quality deterioration of turbot fillets, with C 4 -HSL and C 14 -HSL being the most effective. Moreover, the content decrease of exogenous AHLs was also validated by GC-MS analysis. Further, changes in rhlR transcription levels in P. ﬂuorescens suggest this bacterium can sense environmental AHLs. Finally, molecular docking analysis demonstrates the potential interactions of RhlR protein with various exogenous AHLs. These findings strongly implicate environmental AHLs in turbot spoilage caused by P. ﬂuorescens, suggesting preservation of turbot should not exclusively consider the elimination of SSO-secreted AHLs.